Data Mining: Implementasi Regresi Linear Untuk Prediksi Nilai Ujian - Andriani, Widyastuti; Leong, Hironimus (PROXIES, 2013)
One of the objectives of data mining is prediction based on the pattern of data that already exists. One method used to form linear prediction data is linear regression. Prediction data using linear regression using two variables that can be described in two dimensions. This journal uses linear regression method for the prediction of test scores. Keyword: Regresi Linear, Data Mining, Prediksi